2007
DOI: 10.1007/s10654-007-9107-4
|View full text |Cite
|
Sign up to set email alerts
|

A method to predict the metabolic effects of changes in insulin treatment in subgroups of a large population based patient cohort

Abstract: This case-control study was designed to analyse predictors of the effects on HbA1c levels in 4001 type 1 and type 2 diabetic patients after changing their insulin treatment. Patients from 15 outpatient diabetic clinics were treated with basal insulin and multiple injections of short-acting insulin. The effects on HbA1c of changing from NPH insulin to insulin glargine as basal insulin were studied, compared to patients continuing with NPH insulin. The following possible predictors were examined with multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…Though marginal, there is a higher prevalence of T2D in young men than women (Wild, Roglic et al 2004, Ding, Song et al 2006), likely attributed to the fact that males are more susceptible to insulin resistance than females (van Genugten, Utzschneider et al 2006). Studies have also demonstrated that (i) the insulin analogue glargine causes a significantly greater decrease in HbA1c in males than females (Osterbrand, Fahlen et al 2007) and that (ii) males respond better to sulfonylureas than females (Donnelly, Doney et al 2006), while (iii) females respond more favorably to rosiglitazone than males (Kim, Cha et al 2005). Our understanding of sex dimorphisms in diabetes is compounded by underlying physiological differences which are numerous and include differences in glucose control and energy homeostasis (Basu, Dalla Man et al 2006), insulin disposal and clearance (Jensen, Nielsen et al 2012), regional fat disposition (Geer and Shen 2009, Macotela, Boucher et al 2009), and sex steroid hormones (Shi and Clegg 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though marginal, there is a higher prevalence of T2D in young men than women (Wild, Roglic et al 2004, Ding, Song et al 2006), likely attributed to the fact that males are more susceptible to insulin resistance than females (van Genugten, Utzschneider et al 2006). Studies have also demonstrated that (i) the insulin analogue glargine causes a significantly greater decrease in HbA1c in males than females (Osterbrand, Fahlen et al 2007) and that (ii) males respond better to sulfonylureas than females (Donnelly, Doney et al 2006), while (iii) females respond more favorably to rosiglitazone than males (Kim, Cha et al 2005). Our understanding of sex dimorphisms in diabetes is compounded by underlying physiological differences which are numerous and include differences in glucose control and energy homeostasis (Basu, Dalla Man et al 2006), insulin disposal and clearance (Jensen, Nielsen et al 2012), regional fat disposition (Geer and Shen 2009, Macotela, Boucher et al 2009), and sex steroid hormones (Shi and Clegg 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Current therapeutic options for DPN rely on controlling and treating T2D; however, significant gender dimorphisms in the responsiveness of patients to anti-diabetic drugs have been reported (Kim, Cha et al 2005, Donnelly, Doney et al 2006, Osterbrand, Fahlen et al 2007). These observations highlight the importance of elucidating gender-specific differences in diabetes disease manifestation; a decree which has been iterated by the National Institutes of Health (Clayton and Collins 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently described a similar phenomenon for insulin glargine, and possibly it is due to lower insulin resistance and could indicate a general need of careful optimization of insulin titration in those with high BMI. 8 We have also seen that after the introduction of the new basal insulins and the more frequent use of pumps there was a further decrease of HbA1c. 5,8 In conclusion, this study indicates that insulin lispro generally has a beneficial effect in clinical care in comparison with regular insulin.…”
Section: Lind Et Al 54mentioning
confidence: 78%
“…8 We have also seen that after the introduction of the new basal insulins and the more frequent use of pumps there was a further decrease of HbA1c. 5,8 In conclusion, this study indicates that insulin lispro generally has a beneficial effect in clinical care in comparison with regular insulin. It thus supports the positive mean effects observed in meta-analyses.…”
Section: Lind Et Al 54mentioning
confidence: 78%
See 1 more Smart Citation